2008
DOI: 10.4103/0022-3859.41805
|View full text |Cite
|
Sign up to set email alerts
|

Primary gastrointestinal mucormycosis in an immunocompetent person

Abstract: In the past decade, mucormycosis has emerged as an important lethal infection in diabetics and other immunocompromised hosts. Rhinosinusitis, pansinusitis, rhino-orbital and rhinocerebral are the common classical manifestations of mucormycosis. However, primary gastrointestinal (GI) mucormycosis is an uncommon disease associated with a high mortality rate. Stomach is the most common site involved in GI mucormycosis. Reported cases of GI mucormycosis in an immunocompetent host are very few in the literature. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…Gastrointestinal mucormycosis is uncommon, representing 4–7% of systemic mucormycosis cases, with a mortality of 85% 4,5. Mucormycosis develops in the gastrointestinal (GI) tract iatrogenically or by ingesting fermented foods and herbal/homeopathic remedies 4.…”
Section: Case Reportmentioning
confidence: 99%
See 3 more Smart Citations
“…Gastrointestinal mucormycosis is uncommon, representing 4–7% of systemic mucormycosis cases, with a mortality of 85% 4,5. Mucormycosis develops in the gastrointestinal (GI) tract iatrogenically or by ingesting fermented foods and herbal/homeopathic remedies 4.…”
Section: Case Reportmentioning
confidence: 99%
“…Mucormycosis develops in the gastrointestinal (GI) tract iatrogenically or by ingesting fermented foods and herbal/homeopathic remedies 4. The most common site of GI infection is the stomach, followed by colon, ileum, duodenum, and jejunum 5. Presentation is variable with nonspecific symptoms such as abdominal pain, nausea, fever, and hematochezia; more severe infections present with bowel perforation 5.…”
Section: Case Reportmentioning
confidence: 99%
See 2 more Smart Citations
“…Mucormycosis in an immunocompetent patient has good prognosis (Sridhara et al, 2005;Zhao et al, 2009;Lechevalier et al, 2008;Tehmeena et al, 2007; Jayasuriya et al, 2006;Radner et al, 1995). Therefore, a case of mucormycosis in an immunocompetent patient who died, without autopsy, was suspected to have involved a coexisting malignancy or other disease that immunocompromised the patient (Baradkar et al, 2008;Shiva Prasad et al, 2008). A literature review revealed only seven reported cases of mucormycosis in patients with nonhaematological malignancies (Roden et al, 2005).…”
mentioning
confidence: 99%